Abraham, the nations, and the Hagarite s Jewish, Christian, and Islamic perspectives on kinship with Abraham - Goodman, Martin.; Kooten, Geurt Hendrik van, 1969-; Ruiten, J. van (Themes in Biblical Narrative, 2010)
Jews, Christians and Muslims describe their origins with close reference to the narrative of Abraham, including the complex story of Abraham's relation to Hagar. This volume sketches the history of interpretation of some of the key passages in this narrative, not least the verses which state that in Abraham all the nations of the earth will be blessed. This passage, which features prominently in Christian historiography, is largely disregarded in ancient Judaism, prompting the question how the relation between Abraham and the nations was perceived in Jewish sources. This focus is supplemented with the question how Islamic historiography relates to the Abraham narrative, and in particular to the descent of the Arabs from Abraham through Ishmael and Hagar. In studying the traditional readings of these narratives, the volume offers a detailed yet wide-ranging analysis of important aspects of the accounts of their origins which emerged within the three Abrahamic religions.